Training of Using Quizizz Application to Increase the Arabic Teachers Quality in Pandemic Time - Dian Risky Amalia; Nurul Aisyah; Nasidatul Khusna (Yayasan Payungi Smart Madani, 2023)
Before the Covid-19 pandemic, learning evaluations generally used question sheets in printed form which were done by students and supervised by teachers. However, during the Covid-19 pandemic, it was not possible to use the evaluation sheet in printed form. Evaluation sheets using paper are less effective in their implementation. This makes a demand that Arabic language teachers or educators must be able to optimize the use of website-based applications as an easy means of evaluating learning so that the learning process can be more interesting and challenging. Therefore, the article gave the training of Using Quizezz Application to Increase the Arabic Teachers Quality in Pandemic Time. This Community Service uses the ABCD (Asset-based community development) approach. Through the ABCD approach, community members are facilitated to formulate a change agenda that they consider important and useful. Elementary or Madrasah Ibtidayah Arabic Subject Educators in Metro City as partners have scientific assets and expertise in the Arabic language field who will be assisted to learn about the quizizz application as an effort to become innovative educators. The Quizizz application makes it easy for educators to give questions or exercises online to be more effective and efficient. This training is carried out by the Arabic language teacher community at the elementary/MI education unit level in Metro City. This training prioritizes the utilization of the potential and assets that already exist in Arabic teacher educators